The Importance of Literacy in the World of Education: "How Important is Literacy Really" - Monggun Maulidiya Siregar; M. Joharis; Nova Muhairani Nasution; Yolanda Vera Nicole Sitinjak (International Journal of Educational Development, 2025)
Literacy is a fundamental skill that is very important in the field of education, especially for students in Indonesia. This study aims to explore the understanding of 7th and 8th-grade students regarding the importance of literacy, the challenges they face in improving their literacy skills, and to provide recommendations for enhancing literacy programs in schools. The method used in this research is descriptive qualitative with semi-structured interviews conducted at SMP N 15 Medan. The results of the study indicate that although students are aware of the importance of literacy, they face various challenges, including low reading interest, lack of access to quality reading materials, and minimal environmental support. This research is expected to contribute to the development of more effective literacy strategies in schools through the suggestions and implications provided in this study. Keywords:;;;.